Progress in Photo-Responsive Polypeptide Derived Nano-Assemblies - Yang, Lu; Tang, Houliang; Sun, Hao (Micromachines (Basel), 2018)
Stimuli-responsive polymeric materials have attracted significant attention in a variety of high-value-added and industrial applications during the past decade. Among various stimuli, light is of particular interest as a stimulus because of its unique advantages, such as precisely spatiotemporal control, mild conditions, ease of use, and tunability. In recent years, a lot of effort towards the synthesis of a biocompatible and biodegradable polypeptide has resulted in many examples of photo-responsive nanoparticles. Depending on the specific photochemistry, those polypeptide derived nano-assemblies are capable of crosslinking, disassembling, or morphing into other shapes upon light irradiation. In this mini-review, we aim to assess the current state of photo-responsive polypeptide based nanomaterials. Firstly, those ‘smart’ nanomaterials will be categorized by their photo-triggered events (i.e., crosslinking, degradation, and isomerization), which are inherently governed by photo-sensitive functionalities, including O-nitrobenzyl, coumarin, azobenzene, cinnamyl, and spiropyran. In addition, the properties and applications of those polypeptide nanomaterials will be highlighted as well. Finally, the current challenges and future directions of this subject will be evaluated.